Etiopahtogenesis and Therapeutic Management of Thiamine Responsive Caprine Polioencaphalomalacia - Usha Narayana Pillai (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 2002)
A study on polio encephalomalacia in goats was conducted in the department of Clinical Medicine College of Veterinary and Animal Sciences during the period 1999 to 2002. The occurrence of the disease in Kerala was studied. The study revealed that the disease was reported throughout Kerala with maximum occurrence in the post-monsoon period. The disease was prevalent in all the age groups. Feeding of carbohydrate rich diet was one of the probable predisposing causesfor the development ofPEM. Six apparently healthy goats maintained under identical conditions were utilized for recording normal values. Twenty one confirmed cases of PEM were equally divided into three groups at random. Detailed clinical examination, sampling and analysis of rumen liquor and blood were done before initiation of therapy, 48 and 96 h of study. Therapeutic management of group 1 was by administering thiamine hydrochloride for four days @ 50 mg/kg body weight. (half of the dose intravenously and the other half intra muscularly) whereas in group 11 and III it was supported with oral administration of 500 mg oxytetracycline/animal once (on the day of admission) and 1 gm of thiamine hydrochloride / animal once (on the day of admission) respectively. The characteristic clinical signs were head tilt, lateral deviation of head, nystagmus. circling, staggering gait, pressing of head and lying only on one side. All the symptoms mentioned above were not present in all the animals. Rumen liquor study did not reveal any significant change in pH, physical characters, total volatile fatty acids, copper, cobalt and sulphate levels. Rumen liquor thiamine level was significantly low on the day of admission in all the groups, but became normal by 48 h in group III and by 96 h in other groups. Normal level 'of serum copper, cobalt, magnesium and sulphate confirmed that these electrolytes were not involved in the etiopathogenesis of PEM in Kerala. Significant increase in glucose, lactate, and pyruvate levels were observed on the first day in all the diseased animals. The values decreased steadily after the